Ultrasound manifestations of lobulated ovaries: Case report. Issue 18 (May 2018) - Chen, Tianjiao; Li, Jianchu; Yang, Xiao; Huang, Huifang; Cai, Sheng
Abstract: Rationale: Ultrasound features of lobulated ovaries are rarely described in the literature. Here, we report a case of pathologically proven lobulated ovaries. Patient concerns: A 22-year-old female with irregular menstrual cycles for 9 years came to our hospital because of endless menstruation and anemia for 1 month. Diagnoses: Ultrasound and computed tomography revealed pelvic masses. But diagnosing or excluding neoplasms based on imaging findings was difficult. Interventions: The patient underwent an exploratory laparotomy. Some nodules in the right adnexal region were removed, and a left ovarian biopsy was performed. Outcomes: Pathology results revealed nodular ovarian tissue with cortical fibrosis, but no tumor cells. Lessons: Our case demonstrates ultrasound manifestations of lobulated ovaries and the importance of being acquainted with these features.